(untitled) (Alternautas, 2022)
Chilean extractive development model remains on a neoliberal water-management institutional framework edified by Augusto Pinochet’s dictatorship and perpetuated by the Concertation of Parties for Democracy governments (Tecklin et al. 2011). This model therefore appears as an example of new forms of extractivism in Latin America (Gudynas 2011), which can be defined as a “patrón de acumulación basado en la sobreexplotación de recursos naturales, en gran parte no renovables, así como en la expansión de las fronteras hacia territorios antes considerados como «improductivos»” (Svampa, 2013:33). It was implemented during the dictatorship by means of structural reforms opposed to the Unidad Popular government policies headed by Salvador Allende. Several laws encouraged foreign investments to develop new strategic export industries such as mining, agriculture, hydroelectric energy, forestry or pisciculture (Quiroja 1994). Moreover, the current constitution, enacted in 1980, represents the core of the neoliberal institutional framework currently shaping the Chilean state (Moulian 2002). This article aims to analyze the plurality of water conflicts existing at the watershed level in an extractivist context.